Corrosion fatigue property of 2.25Cr-1Mo steels in a high-temperature sulfide corrosion atmosphere simulating the inside of a pulverized coal-fired boiler - Masahide YOSHIDA (Nihon Kikai Gakkai ronbunshu)
Fatigue cracks have been observed in the boiler water wall tubes of pulverized coal-fired power plants in high-temperature sulfide corrosive environments, and there is concern that thermal fatigue cracks will increase and propagate as the power output of pulverized coal-fired power plants increases to support the massive introduction of variable renewable energy. Therefore, we confirmed the corrosion fatigue characteristics of water wall tube material by fatigue tests in a high-temperature sulfide corrosive environments simulating the inside of the boiler. The corrosion environments were gas condition A, in which iron sulfides mainly occur, gas condition B, in which iron sulfides and oxides mainly occur, and gas condition C, in which iron oxides mainly occur. Note that water vapor was not added due to equipment restrictions. A best-fit curve (regression line) from the corrosion fatigue test results showed that the number of failure cycles (the number of cycles in which the stress range during the test decreased by 25% from the maximum value) was smaller for gas conditions A and B (sulfide corrosion atmosphere) compared to gas condition C (oxide corrosion atmosphere) for the same strain amplitude (calculated from the stroke of the fatigue equipment). We believe that the decrease in the number of failure cycles under gas conditions A and B (sulfidic corrosive environment) is due to the corrosion pits on the specimen surface, which are the starting point of fatigue cracks.